Response of alcohol fermentation strains, mixed fermentation and extremozymes interactions on wine flavor - Zhao, Ling-Zhi; Chen, Jing; Wei, Xiang-Ying; Lin, Bo; Zheng, Feng-Jin; Verma, Krishan K.; Chen, Gan-Lin (Frontiers in Microbiology, 2025)
Winemaking, one of the ancient technologies, is simply the process of converting sugar into alcohol through a complex biochemical reaction. The process of winemaking involves a complex of enological technique that faces a host of challenges in a winery including, inconsistent quality due to chemical and microbiological instability, limited sensory flavor profiles, and concerns met with changing micro-environmental conditions. Fermentation is a metabolic process where the chemical composition of an organic substrate is fragmented via the cellular enzymes under anaerobic conditions. Mixed fermentation, which involves using multiple strains, can enhance the aroma of fermented food, overcome the limitations of single strain fermentation, and improve flavor and quality of food. Mixed fermentation has important applications for agro-food industries, healthcare products and medical sciences. The modern mixed fermentation process showed the enhancement of wine aroma, flavor and taste, reducing volatile acidity and upregulating the phenylethyl acetate concentration through synergistic effect of multiple microorganisms. Key microorganisms in alcohol fermentation, such as yeast, lactic acid and acetic acid bacteria, interact with each other during alcohol fermentation process affects the quality and flavor of the wine. Extremophilic microorganisms have established different molecular strategies to survive amidst the adverse conditions. Biocatalysts isolated by these organisms are termed extremozymes and possess extraordinary properties of salt allowance, thermostability, and cold adaptability. However, the physicochemical and sensory properties of alcohol are important to the quality of end-use products. Therefore, when optimizing fermentation conditions, selecting a right combination of microorganisms is the key to derive better physicochemical and sensory properties. However, the use of mixed fermentation and extremozymes can provide significant insight and potential remedial solutions to overcome these technical problems and shape the final product in more desirable and sustainable ways, challenging the current shortcomings to deliver a more resilient end-products with consistent, flavorful, and a number of what may be considered remedial techniques can be employed to produce an acceptable product to consumers.